How do the habitual sleep patterns of elite female basketball and soccer athletes compare with the general population? - Miles, K. H.; Clark, B.; Mara, J. K.; Fowler, P. M.; Miller, J.; Pumpa, K. L. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To compare the habitual sleep of female basketball and soccer athletes to age- and sex-matched controls and to characterize the sleep of basketball and soccer athletes at different competition locations and on the days surrounding competition.